Solitary fibrous tumor of the adrenal gland: a case report and review of the literature - Shi, Changjie; Shi, Xiuquan; Wu, Ding; Zhang, Ying; Fu, Dian; Xu, Xiaofeng; Cheng, Wen (Frontiers in Surgery, 2024)
Solitary fibrous tumor (SFT) is a rare mesenchymal tumor, probably of fibroblastic origin, mainly in the extremities and pleura. Primary SFT of the adrenal gland is clinically more rare. Here, we report a case of a 47-year-old woman who find a left adrenal mass on physical examination, without any symptoms, and no laboratory abnormalities. Computed tomography (CT) examination of the adrenal gland suggested a round-like soft tissue density shadow in the left adrenal area, unenhanced scan showed uneven density of the mass, with scattered circular-like cystic low-density shadow inside, and enhanced scan showed obvious uneven enhancement. We consider that it is adrenal pheochromocytoma. Ultimately, the patient was treated with laparoscopic left-adrenalectomy, pathological examination suggested the adrenal SFT. We reviewed the previous case reports of adrenal SFT and summarized the clinical characteristics of adrenal SFT combined with the relevant literature. For adrenal tumors with uneven low-density shadow and uneven CT enhancement features, we should consider the differential diagnosis of adrenal SFT.